2012
DOI: 10.3892/mmr.2012.1234
|View full text |Cite
|
Sign up to set email alerts
|

C/EBP homologous protein induces mesangial cell apoptosis under hyperglycemia

Abstract: Abstract. Diabetes mellitus is known to cause kidney impairment; however, the mechanism remains elusive. The aim of this study was to investigate the role of C/EBP homologous protein (CHOP), an important protein in endoplasmic reticulum stress-mediated mesangial cell apoptosis in hyperglycemia. Mesangial cells were cultured in normal (control group) and high glucose medium (high glucose group). TUNEL staining was performed to assess apoptotic cells in the groups. The expression of CHOP and caspase-3 was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(25 reference statements)
1
6
1
Order By: Relevance
“…It is well known that cellular apoptosis can be mediated by the upregulation of apoptosis-related genes (56)(57)(58). Our previous studies found that sublytic C5b-9 complexes induced the apoptosis of GMCs in rats with Thy-1N through IRF-1-dependent caspase 8 expression and activation (22); however, the precise mechanism by which IRF-1 increases caspase 8 expression and activation remains unclear.…”
Section: Discussionmentioning
confidence: 96%
“…It is well known that cellular apoptosis can be mediated by the upregulation of apoptosis-related genes (56)(57)(58). Our previous studies found that sublytic C5b-9 complexes induced the apoptosis of GMCs in rats with Thy-1N through IRF-1-dependent caspase 8 expression and activation (22); however, the precise mechanism by which IRF-1 increases caspase 8 expression and activation remains unclear.…”
Section: Discussionmentioning
confidence: 96%
“…In mesangial cells, ER stress is involved in dysregulation via a variety of mechanisms such as impairment of gap junctional intracellular communication and phenotypic changes (Huang et al, ; Li et al, ). In addition, accumulating evidence suggests that ER stress is closely related to mesangial cell apoptosis (Wang et al, ; Lim et al, ; He et al, ). The present study provides strong evidence that ER stress is one of the main causes of mesangial cell apoptosis according to the following findings: 1) treatment of ADMA, which induces mesangial cell apoptosis, activated three branches of ER stress signaling, 2) thapsigargin treatment increased apoptotic cell death, 3) each of the inhibitors against the three branches of ER stress prevented the ADMA‐induced decrease in MMP, and 4) the inhibitors attenuated ADMA‐induced apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…11, 12, 14 There is growing interest in GMC apoptosis as a potential contributor to the renal lesion. 10, 14, 41, 42 Early research demonstrated that administration of cobra venom factor (CVF) to deplete complement significantly attenuates renal injury in Thy-1N rats, 10, 16 indicating that GMC apoptosis in rat Thy-1N is complement dependent. Our previous studies have revealed that although C5b-9 deposits were found on the membrane of glomerular cells in Thy-1N rats, many glomerular cells deposited with C5b-9 still remained intact, indicating that these C5b-9 complexes are sublytic.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, flow cytometry analysis was performed to detect the cellular apoptosis. 41 In addition, both TUNEL staining (FITC-labeled) and the Ab against C5b-9 (adding Cy3-labeled secondary Ab) were used to label the cells (5 × 10 5 GMCs) at 6 h after sublytic C5b-9 stimulation. Flow cytometry analysis was then performed to detect the cellular apoptosis and C5b-9 deposits on GMC membrane.…”
Section: Methodsmentioning
confidence: 99%